Multiple Functions of the Leucine-Rich Repeat Protein LrrA of Treponema denticola - Ikegami, Akihiko (American Society for Microbiology, 2004)
The gene lrrA, encoding a leucine-rich repeat protein, LrrA, that contains eight consensus tandem repeats of 23 amino acid residues, has been identified in Treponema denticola ATCC 35405. A leucine-rich repeat is a generally useful protein-binding motif, and proteins containing this repeat are typically involved in protein-protein interactions. Southern blot analysis demonstrated that T. denticola ATCC 35405 expresses the lrrA gene, but the gene was not identified in T. denticola ATCC 33520. In order to analyze the functions of LrrA in T. denticola, an lrrA-inactivated mutant of strain ATCC 35405 and an lrrA gene expression transformant of strain ATCC 33520 were constructed. Characterization of the mutant and transformant demonstrated that LrrA is associated with the extracytoplasmic fraction of T. denticola and expresses multifunctional properties. It was demonstrated that the attachment of strain ATCC 35405 to HEp-2 cell cultures and coaggregation with Tannerella forsythensis were attenuated by the lrrA mutation. In addition, an in vitro binding assay demonstrated specific binding of LrrA to a portion of the Tannerella forsythensis leucine-rich repeat protein, BspA, which is mediated by the N-terminal region of LrrA. It was also observed that the lrrA mutation caused a reduction of swarming in T. denticola ATCC 35405 and consequently attenuated tissue penetration. These results suggest that the leucine-rich repeat protein LrrA plays a role in the attachment and penetration of human epithelial cells and coaggregation with Tannerella forsythensis. These properties may play important roles in the virulence of T. denticola.